Coping Strategies at the Time of Diagnosis and Quality of Life 2 Years Later: A Study in Primary Cutaneous Melanoma Patients. Issue 1 (January 2017) - Bonnaud-Antignac, Angélique; Bourdon, Marianne; Dréno, Brigitte; Quéreux, Gaëlle
Abstract : Background: While coping has been found to have time-lagged effects on psychological adjustment in cancer patients, studies addressing this issue are missing in melanoma patients. Objective: The aim of this study was to provide more insight into the links between coping strategies at the time of diagnosis and quality of life (QOL) 2 years later in patients with primary cutaneous melanoma. Methods: Patients who received diagnosis of melanoma (n = 78) were assessed regarding coping strategies within 1 month of diagnosis (T1); their anxiety, depression, control, QOL, and life satisfaction were evaluated 24 months later (T2). Relevant medical and sociodemographic data were collected at T1 and T2. Hierarchical regression analyses were performed. Results: Consistent with the literature, we found that higher positive reframing was associated with greater life satisfaction and that increased behavioral disengagement was related to decreased cognitive functioning. Surprisingly, our results highlighted that higher active coping predicted lower emotional functioning and that greater religious coping was associated with more reports of nausea symptoms. We also noticed that depression was strongly related to QOL beyond the end of interferon α therapy. Conclusion: The findings of the present study suggest that specific coping strategies may have time-lagged effects on QOL when the treatment is completed. Implications for Practice: These findings provide new insights into the coping strategies that could be promoted in coping skills interventions in dermatology units and reveal the significant role of preventive care concerning the posttreatment period.